Seriousness and outcomes of reported adverse drug reactions in old and new antiseizure medications: a pharmacovigilance study using EudraVigilance database - Girgis, Michael Magdy Fahmy; Farkasinszky, Gergely; Fekete, Klára; Fekete, István; Vecsernyés, Miklós; Bácskay, Ildikó; Horváth, László (Frontiers in Pharmacology, 2024)
Epilepsy is a widespread disease requiring long-term drug treatment. The aim of this study was to collect information on reported suspected adverse drug reactions (sADRs) of antiseizure medications (ASMs) and study their seriousness and outcomes in various system organ classifications (SOCs). We intended to compare old and new ASMs' ADRs.Using EudraVigilance (EV) database, we extracted line listings of reported sADRs with different ASMs over the period from January 2012 to December 2021. The list of ASMs was compiled according to the Anatomical therapeutic chemical classification system. The Medical Dictionary for Regulatory Activities version 24.0 was used for determining the SOCs of individual reported preferred terms (PTs) sADRs. In addition, we calculated the Reporting Odds Ratio (ROR), 95% confidence interval (95% CI), p-value (statistically significant if p<0.05) and chi-square statistics.A total of 276,694 reports were contained in the exported line listings which included 1,051,142 individual sADRs reported as PTs such as seizure (3.49%), drug ineffective (2.46%), somnolence (1.32%), dizziness (1.29%) and represented four SOCs: nervous system disorders (19.26%), general disorders and administration site conditions (14.39%), psychiatric disorders (11.29%) and injury, poisoning and procedural complications (9.79). Among patients, the age group between 18 and 64 years had the highest percentage (52.40%), followed by those aged over 64 years (18.75%).Of all the reported PTs, 882,706 (83.98%) had reported seriousness. Old ASMs had a significant positive association with 'caused/prolonged hospitalisation', 'congenital anomaly', 'disabling', 'life threatening' and 'results in death', while new ASMS with 'other medically important condition'. There were 386 (0.04%) PTs related to Sudden Unexpected Death in Epilepsy (SUDEP).In our study, we examined 10 years' reported sADRs of ASMs in the EV international database.The majority of PTs were serious. Old ASMs were generally more commonly associated with undesired outcomes and seriousness. Considering their expected seriousness and outcomes, the safety profile of the different ASMs, can play a cardinal role in the selection of ASMs.